الصدمة النفسية لدى امهات الاطفال بمرض السرطان - عزي, شفاء; سامي, مروة (University of Eloued جامعة الوادي, 2023)
هدفت الدراسة إلى معرفة مدى معاناة أمهات الأطفال المصابين بالسرطان، وتحديد درجة الصدمة النفسية لديهن، وقد تمت هذه الدراسة بالمؤسسة الاستشفائية بولاية الوادي في مصلحة طب الأطفال حيث قمنا خلالها بدراسة حالتين من الأمهات تتراوح أعمارهن بين35 إلى 41 سنة، وتم اختيارهم بدقة مستعملين في ذلك المقابلة ومقياس تروماك لقياس الصدمة النفسية، والذي كان أفضل أداة مقننة لمعرفة ما إذا كان هناك صدمة لدى أمهات الأطفال المصابين بمرض السرطان وتناذرات صدمية متمثلة في تناذر التجنب وتناذر التكرار. وبعد تحليل معطيات مقياس تروماك لصدمة النفسية توصلت الدراسة إلى أن أمهات أطفال مرضى السرطان يعانين من صدمة نفسية، وقد تحققت الفرضية وأظهرت الحالتان أنهما يعانيان صدمة نفسية شديدة. وقد ختمنا دراستنا بجملة من التوصيات في ضوء النتائج المتوصل إليها. الكلمات المفتاحية: الصدمة النفسية، مقياس تروماك، السرطان، الأمهات. Study Summary: The study aimed to determine the extent of suffering experienced by mothers of children with cancer and assess the level of psychological trauma they endure. The study was conducted at the hospital facility in the state of El Oued, in the Pediatric Medicine Department. Two mothers between the ages of 35 and 41 were carefully selected for the study. The Traumatic Event Scale (TES) was utilized as a standardized tool to measure psychological trauma and determine if there is trauma among mothers of children with cancer. Traumatic symptoms were assessed in terms of avoidance and intrusion. After analyzing the data collected through the TES, the study concluded that mothers of children with cancer do experience psychological trauma. The hypothesis was confirmed, as both cases showed severe psychological trauma. The study concluded with a set of recommendations based on the findings. Keywords: psychological trauma, Traumatic Event Scale (TES), cancer, mothers.
تخصص علم نفس